Caregiver and family quality of life for children with fetal alcohol spectrum disorder. (November 2019) - Reid, N.; Moritz, K.M.
Abstract: Background: Fetal alcohol spectrum disorder (FASD) is a common neurodevelopmental condition. Given that individuals with FASD can experience lifelong challenges, one field of research that could be applicable is the paediatric chronic health literature. Aims: The aim of the current study was to investigate the utility of the Pediatric Quality of Life Inventory (PedsQL) Family Impact Module, designed to measure the impact of paediatric chronic health conditions on caregivers and families. Methods and procedures: 109 caregivers of children with FASD completed an online survey that assessed a range of areas including, caregiver and family quality of life, caregiver mental health and child behaviour. Outcomes and results: Overall, caregivers reported the areas most impacted on the PedsQL module were Family Daily Activities and Worry. Caregiver's country of residence, mental health, child gender, and level of child behaviour problems were found to be predictors of caregiver and family quality of life. Conclusions and implications: The results demonstrate that there are multidimensional challenges for caregivers and families. These findings have important implications for policy and practice regarding the provision of supports and services for children with FASD and their families.